DIGITAL TRANSFORMATION IN IMPROVING THE PERFORMANCE OF AGRO INDUSTRIAL SMEs IN INDONESIA - Chairul Hamdani; Yudi Azis; Zulkifli, Zulkifli (Bajang Institute, 2024)
This research seeks to identify and test factors that improve organizational performance towards digital transformation in SMEs in the agro-industrial sector. This study uses a quantitative approach. The population in this research is Indonesian agro-industrial SMEs, totaling 1.68 million units, data source from the Ministry of Industry. The type of sampling used was nonprobability sampling with purposive sampling technique. In determining the number of representative samples, it depends on the number of indicators multiplied by 5 by 10 to obtain a total sample of 380 respondents. This research data consists of primary data. To collect research data, the author can use methods including, observation method, questionnaire method, documentary method. Data analysis in this research used SEM-PLS. The results of this research show that Agility Organizational Culture has a significant influence on Digital Transformation, Business Environment does not have a significant effect on Digital Transformation, Strategic Intelligence has a positive and significant effect on Digital Transformation, Leadership Competencies have a positive and significant effect on Digital Transformation, Agility Organizational Culture has a positive and significant effect on Organizational Performance, Business Environment has a positive and significant effect on Organizational Performance, Strategic Intelligence has a significant effect on Organizational Performance, Leadership Competencies do not have a significant effect on Organizational Performance, Digital Transformation has a significant impact on Organizational Performance